SEISMIC ACTIVITY OF MOUNT EREBUS IN 1981-1988 - カミヌマ, カツタダ /; KAMINUMA, Katsutada; DIBBLE, Ray Russell (National Institute of Polar Research, 1990)
P(論文) Seismic observations by radio-telemetry has continued in the summit area and on the slopes of Erebus Volcano (77°37'S, 167°09'E, 3794m) in Ross Island, Antarctica since 1980. Remarkable changes of seismic activity were recognized before and after the new phase of volcanic activity in September 1984. The activity had been increasing from the early stage of the observations until the new phase in 1984. It then decreased quickly after the activity ended in December 1984. The daily number of earthquakes was over 150 in 1984 and less than 20 in 1988. The volcanic activity of Mount Erebus seemed to become quiet after the 1984 activity. The seismic activities of Mount Erebus in 1981-1988 are divided into the following four stages; 1) Normal High Activity, 2) Preceding the New Phase, 3) New Phase in Activity and 4) Low Seismic Activity. departmental bulletin paper